Superabsorbent polymers based on copolymers of multiple charged monomers
By adjusting the ionization state using copolymers of multiple charged monomers, the shortcomings of existing superabsorbent polymers in terms of absorbability and salt sensitivity under load are solved, and higher absorbability under load and reduced salt sensitivity under load are achieved.
Patent Information
- Application Number
- CN202510149521.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-30
- Publication Date
- 2025-04-11
AI Technical Summary
Existing superabsorbent polymers (SAPs) have shortcomings in absorbability and salt sensitivity under load, making it difficult to use the least material within a wide range of applications.
By using copolymers of multiple charged monomers, the distance between the charged part and the copolymer main chain is adjusted, the ionization state of the remaining AA residues is reasonably designed, the ionization of adjacent charged residues is reduced, the effective pKa of uncharged residues is increased, and the swelling performance is improved.
The superabsorbent polymer is significantly improved under load and reduces its sensitivity to salt, making it more efficient in performance over a wider range of applications.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application date of April 30, 2020, application number 2020801014912, and name “Superabsorbent polymers based on copolymers of multiple charged monomers”. Technical Field
[0002] The present disclosure relates to superabsorbent polymers made from copolymers of multiple charged monomers, wherein the charged moieties of the different charged monomers are at different distances from the main chain of the copolymer. The copolymer-based superabsorbent polymers have significantly improved absorbency under load. The compositions and methods according to the present disclosure can be used in a variety of absorbent products. Background Art
[0003] Superabsorbent polymer (SAP) is a three-dimensional network that can absorb and retain water (or other aqueous media) and physiological fluids such as urine and blood that exceed hundreds of times of its own dry weight, which usually depends on the ion concentration of the aqueous solution. SAP has applications in multiple fields, including medicine, personal care products, biomaterials, biosorbents and agriculture. The first commercial SAP was produced by the alkaline hydrolysis of starch-g-polyacrylonitrile in 1970. Although these polymers can absorb up to 500 g / g of water, they are mechanically weak in their swollen state. SAP was developed for sanitary applications in Japan and the U.S. industry in the early 1980s. It has been found that SAP has the potential to replace fluff, making their use in sanitary products such as baby diapers and sanitary napkins cost-effective.
[0004] The desired characteristics of SAP include high absorption capacity, high and adjustable swelling rate, absorbency under high load, good swelling gel strength, high gel fraction after cross-linking, excellent durability and stability when swelling and during storage, non-toxicity and low cost. Although current hydrogel systems provide good performance in several aspects in these different aspects, there are several disadvantages in various preparations, including low absorbency under pressure, gel blocking (the initial layer of SAP forms a relatively impermeable barrier to subsequent water diffusion and deeper absorption into the material) and high sensitivity to electrolyte solutions. Various strategies have been adopted to address these challenges, including the formation of composite and nanocomposite hydrogels, interpenetrating polymer network (IPN) hydrogels and various surface treatments; However, there is still a need for improvement to enable the use of minimal materials in the widest possible range of applications.
[0005] The nature of the monomers and cross-linking agents, their concentrations and molar ratios are known to be the most important factors affecting the absorption capacity of SAPs. Acrylic acid, acrylamide and methacrylic acid are the most widely used monomers for commercial preparation of SAPs. However, the presence of some residual acrylamide in the gel poses a challenge to the practical use of such hydrogels for human health and personal care products. In contrast, the water absorption and swelling properties of ionic SAPs (e.g. based on acrylic acid or methacrylic acid) are significantly reduced in saline liquids, including physiological fluids such as urine and blood. The reason for this salt sensitivity is that counterions such as sodium ions (Na + ) can effectively shield the polymer backbone charge, leading to condensation of counterions with polymer-bound charged groups and thereby reducing the counterion entropy and direct chain-chain repulsion available to drive the swelling response.
[0006] A number of strategies have been developed for SAP to try to address some of these challenges.
[0007] As a representative example of the approach in the field of zwitterionic copolymer SAPs, Kabiri et al. reported the synthesis of hydrogels based on the zwitterionic monomers [3-(methacrylamido)propyl]dimethyl(3-sulfopropyl)ammonium hydroxide (MPDSAH) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) by solution polymerization (Kabiri et al., Polym AdvTechnol 2005; 16, 659–666). The free swelling in water increased from 2.3 g / g for the sample without AMPS to a maximum swelling of 212.3 g / g with 20 mol % AMPS, above which the swelling decreased again. In 0.9% saline solution, the lowest swelling of 12.6 g / g corresponded to the sample without AMPS, which increased to 32.8 g / g after incorporation of 20 mol % AMPS. Due to the zwitterionic nature of the SAP, the swelling of the hydrogel was relatively independent of pH over a wide pH range; similar near-constant swelling was also observed in environments with various ionic strengths. However, the absorbency under load (AUL) was not measured, and the use of zwitterionic monomers as the primary monomer would result in significantly higher costs for producing SAP for commercial products.
[0008] As a representative example of the approach in the field of nanocomposite SAPs, Chen et al. synthesized superabsorbent hydrogels by solution copolymerization of partially neutralized acrylic acid and AMPS in the presence of a hydrophilic nanosized clay Laponite XLG to improve the gel's shape stability and mechanical properties (Chen et al., Appl Mech Mater 2013; 427-429: 364-367). Free swelling was observed to increase significantly with increasing AMPS, with the free swelling ratio increasing from 460 g / g xerogel for AA-only hydrogels to 750 g / g xerogel when the AMPS:AA molar ratio was 1. Further small improvements in water binding and significant improvements in gel shape stability were observed upon incorporation of clay up to 20 mol% of the total monomer content, consistent with a balance between adding highly charged and hygroscopic fillers (increased adsorption capacity) and introducing physical crosslinking into the system (reduced adsorption capacity). However, the interaction between nanoscale fillers and bulk gel is challenging for engineers, where the balance between higher gel-filler interaction (increased physical cross-linking and thus reduced swelling) and lower gel-filler interaction (filler aggregation) is critical to control to achieve the desired combination of higher strength and high swelling.
[0009] It is known that the absorbency of saline under load (AUL) can be improved by surface crosslinking reactions between the functional groups of SAP and suitable surface crosslinking agents. Surface crosslinking helps to improve the local mechanics of SAP particles at the particle surface while also reducing the "gel blocking" typically observed with swollen particles, which poses a transport challenge for water to enter the SAP deeper within the SAP pad. Generally, higher crosslinking density on the surface of SAP particles imparts better AUL properties. Bifunctional compounds such as diglycidol and diols are mainly used for SAP surface treatment. Epoxysilane compounds such as 3-glycidylpropoxytrimethoxysilane (GPS) are also used for surface modification of SAP. This compound can increase the AUL through two mechanisms: reaction of carboxylic acid with the epoxy groups of GPS and oligomerization of siloxane on the surface of SAP particles. However, surface crosslinking introduces additional processing steps and can increase the amount of leachable compounds from the SAP unless the residual crosslinker is thoroughly removed from the hydrogel.
[0010] It is also known that multifunctional crosslinkers can be used not only to enhance mechanical strength but also introduce other advantages to SAP due to their branched structure. For example, Ghasri et al. synthesized glycerol-lactic acid-based star-shaped modifiers (SMs) for surface modification of sanitary SAP hydrogels to increase saline-AUL and swollen gel strength. The surface treatment resulted in an increase in AUL of up to 28% in the modified SAP (M. Ghasri et al., Polym Adv Technol., 2018; 1-10). Compared with the intact SAP (f = 0.84 for NaCl and f = 0.90 for CaCl 2 f = 0.95–0.97) compared to the modified samples in NaCl (f = 0.7) and CaCl 2 The lower salt sensitivity factor (f) was shown in the samples (f = 0.93–0.95), which was attributed to the chelating effect induced by such multifunctional modifiers. The deionized water-free swelling capacity of intact SAP was about 366 g / g; however, the 11 Surface cross-linking (SM contains one LA molecule in each arm) leads to Q DW The values decreased (to 249 and 219 g / g using 0.5 g and 1.5 g of cross-linker, respectively) 。 Thus, surface crosslinking using branched crosslinkers improves the AUL of the hydrogel rather than the free water binding capacity. Branched crosslinkers are also synthetically more complex and expensive to prepare, which is a key consideration for commercial applications in disposable products such as sanitary pads or diapers.
[0011] As an alternative to these strategies, this study discloses the rational engineering of the structure of SAP-containing polymers to optimize the number of residues in the SAP that are ionized and thus can induce Donnan equilibrium / direct chain repulsion.
[0012] Conventional superabsorbent materials (SAMs) are mainly made of two types of polymers: synthetic polymers and natural polymers. In general, synthetic superabsorbent polymers are charged polyelectrolytes, such as polyacrylic acid (PAA), polyvinyl sulfonic acid, polyvinyl phosphoric acid salts and partially hydrolyzed maleic anhydride copolymers. Natural polymers include both neutral polymers and charged polymers, such as carboxymethyl cellulose, sodium alginate, chitosan salts and modified starches. All of these known SAMs have substantial limitations. For example, the most widely used SAMs based on commercial PAA have limited absorbency under load (AUL) and are also very sensitive to salt.
[0013] Conventional wisdom holds that SAMs based on polymers with lower molecular weight charged monomers should have higher AULs than SAMs based on polymers with higher molecular weight charged monomers.
[0014] In the present disclosure, it is surprisingly found that only a small portion (<20%) of the total mass in PAA-based SAM particles contributes significantly to osmotic pressure and electrical repulsion, which are the main positive driving forces for SAM swelling under load. For PAA-based SAM particles, those unneutralized acrylic acid monomers (AA) and neutralized acrylic acid sodium salts in an ion pair state do not contribute significantly to osmotic pressure and electrical repulsion.
[0015] It was also surprisingly found that even at pH values where "complete" effective ionization is expected, there is a low degree of ionization (7%-8%) in AA-based SAPs. This lower level of ionization significantly limits the final water content, and therefore limits the efficacy of conventional AA-based SAPs. Therefore, by changing the type of charge present and the distance between the charges present (between the charged monomer residues within the constituent polymer chains and between the charges on the backbone and individual monomer residues), ionization and therefore improved swelling can be achieved.
[0016] It was also surprisingly found that the AUL of SAMs based on copolymers of differently charged monomers depends significantly on the distance between the charged center and the polymer backbone.
[0017] These findings are applicable to a variety of homopolyelectrolyte-based SAM systems. Homopolyelectrolyte-based SAMs are very sensitive to salt, which results in lower absorption of aqueous liquids containing high salt concentrations.
[0018] Described herein are SAMs made from copolymers of multiple charged monomers, wherein the charged moieties of the different charged monomers are at different distances from the copolymer backbone. The copolymer-based SAM particles have significantly improved absorbency under load.
[0019] Compositions and methods according to the present disclosure can be used in a variety of absorbent products.
[0020] Public Purpose
[0021] The purpose of the present disclosure is to address the low ionization level of AA-based SAPs by copolymerizing small portions of different hydrophilic comonomers into the AA-based SAP backbone using free radical polymerization techniques. Such comonomers are used to rationally design the ionization state of the remaining AA residues by physically spacing the ionizable monomers apart and thereby reducing the ionization of adjacent charged residues, thereby increasing the effective pK of the remaining uncharged residues. a The polyelectrolyte effect. Summary of the invention
[0022] In one aspect, there is provided a superabsorbent polymer comprising
[0023] A copolymer comprising
[0024] A major portion of low molecular weight monomers, each of which individually comprises
[0025] Main chain and charged parts;
[0026] a minor portion of high molecular weight monomers, each of which individually comprises a backbone and a charged moiety; and
[0027] optional cross-linking agent;
[0028] The average distance between the main chain and the charged part of each individual low molecular weight monomer is smaller than the average distance between the main chain and the charged part of each individual high molecular weight monomer.
[0029] In another aspect, there is provided a method for preparing a superabsorbent polymer, the superabsorbent polymer comprising
[0030] A copolymer comprising
[0031] a major portion of low molecular weight monomers, each of which individually comprises a backbone and a charged moiety;
[0032] a minor portion of high molecular weight monomers, each of which individually comprises a backbone and a charged moiety; and
[0033] optional cross-linking agent;
[0034] wherein the average distance between the main chain and the charged moiety of each individual low molecular weight monomer is less than the average distance between the main chain and the charged moiety of each individual high molecular weight monomer, the method comprising:
[0035] forming a mixture comprising
[0036] Solvents;
[0037] A low molecular weight monomer comprising a backbone and a charged moiety;
[0038] a high molecular weight monomer comprising a backbone and a charged moiety; and
[0039] Optional cross-linking agent
[0040] Provoke a reaction; and
[0041] The mixture is reacted.
[0042] In yet another aspect, there is provided a method of using a superabsorbent polymer, the superabsorbent polymer comprising
[0043] A copolymer comprising
[0044] a major portion of low molecular weight monomers, each of which individually comprises a backbone and a charged moiety;
[0045] a minor portion of high molecular weight monomers, each of which individually comprises a backbone and a charged moiety; and
[0046] optional cross-linking agent;
[0047] Wherein the average distance between the backbone and the charged moiety of each individual low molecular weight monomer is less than the average distance between the backbone and the charged moiety of each individual high molecular weight monomer, the method comprising using the superabsorbent polymer in a consumer product. DETAILED DESCRIPTION
[0048] The superabsorbent polymer according to the present disclosure comprises a copolymer comprising a major portion of low molecular weight monomers, each of which individually comprises a main chain and a charged portion; a minor portion of high molecular weight monomers, each of which individually comprises a main chain and a charged portion; and an optional crosslinking agent. The average distance between the main chain and the charged portion of each individual low molecular weight monomer is less than the average distance between the main chain and the charged portion of each individual high molecular weight monomer.
[0049] In some embodiments, the copolymer comprises two or more different types of monomers. In some embodiments, the copolymer comprises three or more different types of monomers. In some embodiments, the copolymer comprises four or more different types of monomers. In some embodiments, the copolymer comprises five or more different types of monomers. In some embodiments, the copolymer comprises six or more different types of monomers.
[0050] In some embodiments, the copolymer comprises one or more different kinds of low molecular weight monomers. In some embodiments, the copolymer comprises two or more different kinds of low molecular weight monomers. In some embodiments, the copolymer comprises three or more different kinds of low molecular weight monomers.
[0051] In some embodiments, the copolymer comprises one or more different types of high molecular weight monomers. In some embodiments, the copolymer comprises two or more different types of high molecular weight monomers. In some embodiments, the copolymer comprises three or more different types of high molecular weight monomers.
[0052] In some embodiments, the copolymer lacks a structured ordered arrangement of low molecular weight monomers and high molecular weight monomers. In some embodiments, the copolymer is as random as possible. In some embodiments, the probability of finding a monomer residue of a given type at a specific point along the polymer backbone is approximately equal to the mole fraction of the monomer residue in the polymer backbone.
[0053] In some embodiments, the copolymer does not include a block copolymer of a low molecular weight monomer and a high molecular weight monomer. In some embodiments, the copolymer does not include an alternating copolymer of a low molecular weight monomer and a high molecular weight monomer. In some embodiments, the copolymer does not include a graft copolymer of a low molecular weight monomer and a high molecular weight monomer.
[0054] In some embodiments, the major portion is greater than about 50 mol%, greater than about 51 mol%, greater than about 52 mol%, greater than about 53 mol%, greater than about 54 mol%, greater than about 55 mol%, greater than about 56 mol%, greater than about 57 mol%, greater than about 58 mol%, greater than about 59 mol%, greater than about 60 mol%, greater than about 61 mol%, greater than about 62 mol%, greater than about 63 mol%, greater than about 64 mol%, greater than about 65 mol%, greater than about 66 mol%, greater than about 67 mol%, greater than about 68 mol%, greater than about 69 mol%, greater than about 70 mol%, greater than about 71 mol%, greater than about 72 mol%. , greater than about 73 mol %, greater than about 74 mol %, greater than about 75 mol %, greater than about 76 mol %, greater than about 77 mol %, greater than about 78 mol %, greater than about 79 mol %, greater than about 80 mol %, greater than about 81 mol %, greater than about 82 mol %, greater than about 83 mol %, greater than about 84 mol %, greater than about 85 mol %, greater than about 86 mol %, greater than about 87 mol %, greater than about 88 mol %, or greater than about 89 mol %, greater than 90 mol %, greater than about 91 mol %, greater than about 92 mol %, greater than about 93 mol %, greater than about 94 mol %, or greater than about 95 mol % of the copolymer.
[0055] In some embodiments, the major portion is present in an amount greater than about 60 mole percent of the copolymer.
[0056] In some embodiments, the minor portion is greater than about 5 mol, greater than about 6 mol, greater than about 7 mol, greater than about 8 mol, greater than about 9 mol, greater than about 10 mol, greater than about 11 mol, greater than about 12 mol, greater than about 13 mol, greater than about 14 mol, greater than about 15 mol, greater than about 16 mol, greater than about 17 mol, greater than about 18 mol, greater than about 19 mol, greater than about 20 mol, greater than about 21 mol, greater than about 22 mol, greater than about 23 mol, greater than about 24 mol, greater than about 25 mol, greater than about 26 mol, greater than about 27 mol, greater than about 28 mol, greater than about 29 mol, greater than about 30 mol, greater than about 31 mol, greater than about 32 mol, greater than about 33 mol, greater than about 34 mol, greater than about 35 mol, greater than about 36 mol, greater than about 37 mol, greater than about 38 mol, greater than about 39 mol, greater than about 40 mol, greater than about 41 mol, greater than about 42 mol, greater than about 43 mol, greater than about 44 mol %, greater than about 47 mol %, greater than about 48 mol %, greater than about 49 mol %, greater than about 50 mol %, greater than about 51 mol %, greater than about 52 mol %, greater than about 53 mol %, greater than about 54 mol %, greater than about 55 mol %, greater than about 56 mol %, greater than about 57 mol %, greater than about 58 mol %, greater than about 59 mol %, greater than about 60 mol %, greater than about 61 mol %, greater than about 62 mol %, greater than about 63 mol %, greater than about 64 mol %, greater than about 65 mol %, greater than about 66 mol %, greater than about 67 mol %, greater than about 68 mol %, greater than about 69 mol %, greater than about 70 mol %, greater than about 71 mol %, greater than about
[0057] In some embodiments, the minor portion is less than about 5 mol%, less than about 6 mol%, less than about 7 mol%, less than about 8 mol%, less than about 9 mol%, less than about 10 mol%, less than about 10 mol%, less than about 11 mol%, less than about 12 mol%, less than about 13 mol%, less than about 14 mol%, less than about 15 mol%, less than about 16 mol%, less than about 17 mol%, less than about 18 mol%, less than about 19 mol%, less than about 20 mol%, less than about 21 mol%, less than about 22 mol%, less than about 23 mol%, less than about 24 mol%, less than about 25 mol%, less than about 26 mol%, less than about 27 mol%, less than about 28 mol%, less than about 29 mol%, less than about 30 mol%, less than about 31 mol%, less than about 32 mol%, less than about 33 mol%, less than about 34 mol%, less than about 35 mol%, less than about 36 mol%, less than about 37 mol%, less than about 38 mol%, less than about 39 mol%, less than about 40 mol%, less than about 41 mol%, less than about 42 mol%, less than about 43 mol%, less than about 44 mol%, less than about 45 mol%, less than about 46 mol%, less than about 47 mol%, less than about 48 mol%, less than about 49 mol%, less than about 50 mol%, less than about 51 mol%, less than about 52 mol%, less than about 53 mol%, less than about 54 mol%, less than about 55 mol%, less than about 56 mol%, less than about 57 mol%, less than about 58 mol%, less than about %, less than about 27 mol%, less than about 28 mol%, less than about 29 mol%, less than about 30 mol%, less than about 31 mol%, less than about 32 mol%, less than about 33 mol%, less than about 34 mol%, less than about 35 mol%, less than about 36 mol%, less than about 37 mol%, less than about 38 mol%, less than about 39 mol%, less than about 40 mol%, less than about 41 mol%, less than about 42 mol%, less than about 43 mol%, less than about 44 mol%, less than about 45 mol%, less than about 46 mol%, less than about 47 mol%, less than about 48 mol%, or less than about 49 mol% of the copolymer is present.
[0058] In some embodiments, the minor moiety is present in an amount less than about 40 mole percent of the copolymer.
[0059] In some embodiments, the main part is present in an amount greater than about 50 mol% of the copolymer, and the minor part is present in an amount less than about 50 mol% of the copolymer. In some embodiments, the main part is present in an amount greater than about 55 mol% of the copolymer, and the minor part is present in an amount less than about 45 mol% of the copolymer. In some embodiments, the main part is present in an amount greater than about 60 mol% of the copolymer, and the minor part is present in an amount less than about 40 mol% of the copolymer. In some embodiments, the main part is present in an amount greater than about 65 mol% of the copolymer, and the minor part is present in an amount less than about 35 mol% of the copolymer. In some embodiments, the main part is present in an amount greater than about 70 mol% of the copolymer, and the minor part is present in an amount less than about 30 mol% of the copolymer. In some embodiments, the main part is present in an amount greater than about 75 mol% of the copolymer, and the minor part is present in an amount less than about 25 mol% of the copolymer. In some embodiments, the major portion is present in an amount greater than about 80 mol % of the copolymer, and the minor portion is present in an amount less than about 20 mol % of the copolymer. In some embodiments, the major portion is present in an amount greater than about 85 mol % of the copolymer, and the minor portion is present in an amount less than about 15 mol % of the copolymer. In some embodiments, the major portion is present in an amount greater than about 90 mol % of the copolymer, and the minor portion is present in an amount less than about 10 mol % of the copolymer. In some embodiments, the major portion is present in an amount greater than about 95 mol % of the copolymer, and the minor portion is present in an amount less than about 5 mol % of the copolymer.
[0060] In some embodiments, the major portion is present in an amount greater than about 60 mole percent of the copolymer, and the minor portion is present in an amount less than about 40 mole percent of the copolymer.
[0061] In some embodiments, the superabsorbent polymer is in a form selected from the group consisting of particles, gels, fibers, beads, liquids, solids, pastes, or combinations thereof. In some embodiments, the superabsorbent polymer is a gel. In some embodiments, the superabsorbent polymer is a particle.
[0062] In some embodiments, the superabsorbent polymer is in the form of a diameter ranging from about 100 μm to about 1000 μm, from about 100 μm to about 900 μm, from about 100 μm to about 800 μm, from about 100 μm to about 700 μm, from about 100 μm to about 600 μm, from about 100 μm to about 500 μm, from about 100 μm to about 400 μm, from about 100 μm to about 300 μm, or from about 100 μm to about 200 μm. In some embodiments, the superabsorbent polymer is in the form of a diameter ranging from about 200 μm to about 900 μm, from about 300 μm to about 800 μm, from about 400 μm to about 700 μm, or from about 500 μm to about 600 μm.
[0063] In some embodiments, the superabsorbent polymer is in the form of a particle having a diameter ranging from about 300 μm to about 600 μm.
[0064] In some embodiments, the superabsorbent polymer is a particle having a diameter in the range of about 100 μm to about 1000 μm. In some embodiments, the superabsorbent polymer is a particle having a diameter in the range of about 300 μm to about 600 μm.
[0065] In some embodiments, the superabsorbent polymer does not comprise a crosslinking agent. In some embodiments, the superabsorbent polymer comprises one or more crosslinking agents. In some embodiments, the superabsorbent polymer comprises two or more crosslinking agents.
[0066] In some embodiments, the superabsorbent polymer comprises a crosslinker selected from the group consisting of methylene (bis)acrylamide (MBAA), poly(ethylene glycol diacrylate) (PEGDA), ethylene glycol diacrylate (EGDA), ethylene glycol dimethacrylate (EGDMA), poly(ethylene glycol dimethacrylate) (PEGDMA), and combinations thereof.
[0067] In some embodiments, the superabsorbent polymer is slightly crosslinked. In some embodiments, the superabsorbent polymer has a crosslinker density in the range of about 0.1 mol % to about 1 mol %. In some embodiments, the superabsorbent polymer has a crosslinker density in the range of about 0.2 mol % to about 1 mol %.
[0068] In some embodiments, the superabsorbent polymer is surface cross-linked.
[0069] In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 4.5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 4.0 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 3.5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 3.0 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 2.5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 2.0 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual low molecular weight monomer is less than about 1.5 angstroms.
[0070] In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 5.5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 6 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 6.5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 7 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 7.5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 8 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 8.5 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 9 angstroms. In some embodiments, the average distance between the main chain and the charged part of each individual high molecular weight monomer is greater than about 9.5 angstroms. In some embodiments, the average distance between the backbone and the charged moiety of each individual high molecular weight monomer is greater than about 10 angstroms.
[0071] In some embodiments, the average distance between the backbone and the charged moiety of each individual low molecular weight monomer is less than about 5 angstroms, and the average distance between the backbone and the charged moiety of each individual high molecular weight monomer is greater than about 5 angstroms.
[0072] In some embodiments, the main portion of the low molecular weight monomers each comprising a main chain and a charged portion individually comprises a low molecular weight monomer having a molecular weight of less than about 150 g / mol. In some embodiments, the main portion of the low molecular weight monomers each comprising a main chain and a charged portion individually comprises a low molecular weight monomer having a molecular weight of less than about 125 g / mol. In some embodiments, the main portion of the low molecular weight monomers each comprising a main chain and a charged portion individually comprises a low molecular weight monomer having a molecular weight of less than about 100 g / mol. In some embodiments, the main portion of the low molecular weight monomers each comprising a main chain and a charged portion individually comprises a low molecular weight monomer having a molecular weight of less than about 75 g / mol. In some embodiments, the main portion of the low molecular weight monomers each comprising a main chain and a charged portion individually comprises a low molecular weight monomer having a molecular weight of less than about 50 g / mol. In some embodiments, the main portion of the low molecular weight monomers each comprising a main chain and a charged portion individually comprises a low molecular weight monomer having a molecular weight of less than about 25 g / mol.
[0073] In some embodiments, the minor portion of the high molecular weight monomers each comprising a main chain and a charged portion individually comprises a high molecular weight monomer having a molecular weight greater than about 150 g / mol. In some embodiments, the minor portion of the high molecular weight monomers each comprising a main chain and a charged portion individually comprises a high molecular weight monomer having a molecular weight greater than about 200 g / mol. In some embodiments, the minor portion of the high molecular weight monomers each comprising a main chain and a charged portion individually comprises a high molecular weight monomer having a molecular weight greater than about 250 g / mol. In some embodiments, the minor portion of the high molecular weight monomers each comprising a main chain and a charged portion individually comprises a high molecular weight monomer having a molecular weight greater than about 300 g / mol. In some embodiments, the minor portion of the high molecular weight monomers each comprising a main chain and a charged portion individually comprises a high molecular weight monomer having a molecular weight greater than about 350 g / mol. In some embodiments, the minor portion of the high molecular weight monomers each comprising a main chain and a charged portion individually comprises a high molecular weight monomer having a molecular weight greater than about 400 g / mol. In some embodiments, the minor portion of the high molecular weight monomers each comprising a main chain and a charged portion individually comprises a high molecular weight monomer having a molecular weight greater than about 450 g / mol. In some embodiments, the minor portion of high molecular weight monomers that each individually comprise a backbone and a charged moiety comprises high molecular weight monomers having a molecular weight greater than about 500 g / mol.
[0074] In some embodiments, the major portion of low molecular weight monomers, each individually comprising a backbone and a charged moiety, comprises low molecular weight monomers having a molecular weight less than about 150 g / mol, and the minor portion of high molecular weight monomers, each individually comprising a backbone and a charged moiety, comprises high molecular weight monomers having a molecular weight greater than about 150 g / mol.
[0075] In some embodiments, the main portion of the low molecular weight monomers each individually comprising a main chain and a charged portion comprises a low molecular weight monomer having 1, 2, 3, 4 or 5 carbon atoms. In some embodiments, the main portion of the low molecular weight monomers each individually comprising a main chain and a charged portion comprises a low molecular weight monomer having 3, 4 or 5 carbon atoms. In some embodiments, the main portion of the low molecular weight monomers each individually comprising a main chain and a charged portion comprises a low molecular weight monomer having 1, 2, 3 or 4 oxygen atoms. In some embodiments, the main portion of the low molecular weight monomers each individually comprising a main chain and a charged portion comprises a low molecular weight monomer having 2, 3 or 4 oxygen atoms.
[0076] In some embodiments, the minor portion of high molecular weight monomers, each individually comprising a backbone and a charged moiety, comprises a high molecular weight monomer having 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 carbon atoms. In some embodiments, the minor portion of high molecular weight monomers, each individually comprising a backbone and a charged moiety, comprises a high molecular weight monomer having 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 oxygen atoms. In some embodiments, the minor portion of high molecular weight monomers, each individually comprising a backbone and a charged moiety, comprises a high molecular weight monomer having 2, 3, 4, 5, 6, 7, 8, 9, or 10 oxygen atoms.
[0077] In some embodiments, the major portion of the low molecular weight monomers that each individually comprise a backbone and a charged moiety comprises low molecular weight monomers having a net negative charge. In some embodiments, the major portion of the low molecular weight monomers that each individually comprise a backbone and a charged moiety comprises low molecular weight monomers having a net positive charge.
[0078] In some embodiments, the main part of the low molecular weight monomers that each individually comprises a backbone and a charged portion comprises a low molecular weight monomer having one negative charge or a positive charge. In some embodiments, the main part of the low molecular weight monomers that each individually comprises a backbone and a charged portion comprises a low molecular weight monomer having two negative charges or positive charges.
[0079] In some embodiments, the minor portion of high molecular weight monomers that each individually comprise a backbone and a charged moiety comprises high molecular weight monomers having a net negative charge. In some embodiments, the minor portion of high molecular weight monomers that each individually comprise a backbone and a charged moiety comprises high molecular weight monomers having a net positive charge.
[0080] In some embodiments, copolymers include low molecular weight monomers and high molecular weight monomers with the same amount of negative charge. In some embodiments, copolymers include low molecular weight monomers and high molecular weight monomers, wherein the low molecular weight monomers have more negative charge than the high molecular weight monomers. In some embodiments, copolymers include low molecular weight monomers and high molecular weight monomers, wherein the low molecular weight monomers have less negative charge than the high molecular weight monomers.
[0081] In some embodiments, the minor portion of high molecular weight monomers, each individually comprising a backbone and a charged portion, comprises a high molecular weight monomer selected from the group consisting of: 2-acrylamido-2-methylpropane sulfonic acid, 3-sulfopropyl methacrylate potassium salt, 3-sulfopropyl acrylate potassium salt, acrylate or methacrylate monomers with tethered sulfate groups and salts thereof, salts of vinyl-linker-acid units, salts of vinyl-linker-acid units wherein the linker has a length of at least 3 angstroms, vinyl sulfate monomers, and combinations thereof.
[0082] In some embodiments, the major portion of the low molecular weight monomers that each individually comprise a backbone and a charged moiety comprises a low molecular weight monomer selected from the group consisting of acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl phosphoric acid, partially hydrolyzed maleic anhydride, and combinations thereof.
[0083] In some embodiments, the copolymer does not include zwitterionic charged monomers. In some embodiments, the copolymer does not include nonionic monomers.
[0084] In some embodiments, the copolymer is synthesized according to a method selected from the group consisting of free radical polymerization, anionic polymerization, controlled radical polymerization methods, atom transfer radical polymerization (ATRP), nitroxide-mediated radical polymerization (NMP), reversible addition-fragmentation chain transfer polymerization (RAFT), and combinations thereof. In some embodiments, the copolymer is synthesized according to free radical polymerization.
[0085] In some embodiments, free radicals can be generated by photolysis, thermal decomposition, or ambient redox conditions.
[0086] In some embodiments, the copolymer is synthesized according to a method comprising forming a mixture comprising a solvent, a low molecular weight monomer comprising a backbone and a charged moiety, a high molecular weight monomer comprising a backbone and a charged moiety, and an optional crosslinker; initiating a reaction; and reacting the mixture.
[0087] In some embodiments, the method step of initiating the reaction comprises adding an initiator, a accelerator, or a combination thereof to the mixture. In some embodiments, the initiator is an oxidizing agent.
[0088] In some embodiments, the initiator is an organic compound. In some embodiments, the initiator is selected from the group consisting of azo compounds, organic peroxide compounds, organic persulfate compounds, and combinations thereof. In some embodiments, the initiator is an azo compound. In some embodiments, the initiator is an organic peroxide compound. In some embodiments, the initiator is an organic persulfate compound.
[0089] In some embodiments, the initiator is an inorganic compound. In some embodiments, the initiator is selected from the group consisting of inorganic peroxide compounds, metal reducing agents, iron, chromium, palladium, titanium, cobalt, copper, and combinations thereof. In some embodiments, the initiator is an inorganic peroxide compound. In some embodiments, the initiator is selected from the group consisting of potassium persulfate, ammonium persulfate, and combinations thereof. In some embodiments, the reduction of hydrogen peroxide or alkyl hydroperoxide can be by iron or other reducing agents such as Cr 2+ 、V 2+ 、Ti 3+ 、Co 2+ or Cu + conduct.
[0090] In some embodiments, the initiator is an oxidizing agent. In some embodiments, the initiator is a persulfate. In some embodiments, the initiator is selected from the group consisting of potassium persulfate, ammonium persulfate, and combinations thereof.
[0091] In some embodiments, the promoter is an organic compound. In some embodiments, the promoter is an organic base. In some embodiments, the promoter is tetramethylethylenediamine (TEMED). In other embodiments, the promoter is sodium pyrosulfite (SPS). In some embodiments, no promoter is used. In some embodiments, the promoter is selected from the group consisting of an organic compound, an organic base, TEMED, SPS, no promoter, and combinations thereof.
[0092] In some embodiments, the method step of reacting the mixture comprises reacting the mixture in an inert atmosphere. In some embodiments, the method step of reacting the mixture comprises reacting the mixture in a static inert atmosphere. In some embodiments, the method step of reacting the mixture comprises reacting the mixture in a dynamic inert atmosphere. In some embodiments, the method step of reacting the mixture comprises reacting the mixture under an inert gas flow.
[0093] In some embodiments, the method step of reacting the mixture comprises reacting the mixture in a mixture selected from the group consisting of N 2 , CO 2 , rare gases, helium, neon, argon, krypton, xenon and combinations thereof. In some embodiments, the method step of reacting the mixture comprises reacting the mixture under N 2react in an inert atmosphere.
[0094] In some embodiments, the method step of reacting the mixture includes heating the mixture. In some embodiments, the method step of reacting the mixture includes heating the mixture to a temperature in the range of about 20 ° C to about 100 ° C. In some embodiments, the method step of reacting the mixture includes heating the mixture to a temperature in the range of about 30 ° C to about 100 ° C. In some embodiments, the method step of reacting the mixture includes heating the mixture to a temperature in the range of about 40 ° C to about 100 ° C. In some embodiments, the method step of reacting the mixture includes heating the mixture to a temperature in the range of about 50 ° C to about 100 ° C. In some embodiments, the method step of reacting the mixture includes heating the mixture to a temperature in the range of about 60 ° C to about 100 ° C. In some embodiments, the method step of reacting the mixture includes heating the mixture to a temperature in the range of about 70 ° C to about 100 ° C.
[0095] In some embodiments, the method step of reacting the mixture comprises heating the mixture to a temperature in the range of about 20° C. to about 90° C. In some embodiments, the method step of reacting the mixture comprises heating the mixture to a temperature in the range of about 30° C. to about 80° C. In some embodiments, the method step of reacting the mixture comprises heating the mixture to a temperature in the range of about 40° C. to about 70° C.
[0096] In some embodiments, the method step of reacting the mixture comprises heating the mixture to a temperature in the range of about 20° C. to about 40° C. In some embodiments, the method step of reacting the mixture comprises heating the mixture to about 40° C. In some embodiments, the method step of reacting the mixture comprises heating the mixture to about 70° C.
[0097] In some embodiments, the method further comprises drying the reaction product. In some embodiments, the method further comprises drying the reaction product in an oven. In some embodiments, the method further comprises drying the reaction product at a temperature in the range of about 50 ° C to about 100 ° C. In some embodiments, the method further comprises drying the reaction product at a temperature in the range of about 60 ° C to about 100 ° C. In some embodiments, the method further comprises drying the reaction product at a temperature in the range of about 70 ° C to about 100 ° C. In some embodiments, the method further comprises drying the reaction product at a temperature in the range of about 80 ° C to about 100 ° C. In some embodiments, the method further comprises drying the reaction product at a temperature in the range of about 60 ° C to about 90 ° C. In some embodiments, the method further comprises drying the reaction product at a temperature in the range of about 70 ° C to about 90 ° C.
[0098] In some embodiments, the method further comprises drying the reaction product at a temperature of about 85°C.
[0099] In some embodiments, the method further comprises grinding the reaction product.In some embodiments, the method further comprises grinding the reaction product with a grinding device selected from the group consisting of a mechanical stirrer, a coffee grinder, a crusher, a pulverizer, a grinder, a mill, and combinations thereof.
[0100] In some embodiments, the ability of a polymer to absorb fluid under a static load can be measured as the Absorbency Under Load (AUL).A typical AUL test format can be used.
[0101] In some embodiments, the ability of a pre-swollen polymer to retain water under force can be measured as the Centrifuge Retention Capacity (CRC). A typical CRC test format can be used.
[0102] In some embodiments, superabsorbent polymers are used in consumer products or superabsorbent materials. In some embodiments, consumer products or superabsorbent materials comprise superabsorbent polymers.
[0103] In some embodiments, methods of using superabsorbent polymers include using the superabsorbent polymers in consumer products or superabsorbent materials.
[0104] In some embodiments, the consumer product is selected from the group consisting of cloth products, diapers, feminine hygiene napkins, and disposable mattress pads.
[0105] Example
[0106] Without further elaboration, it is believed that one skilled in the art using the preceding description can utilize the present invention to its fullest extent.Therefore, the following examples are to be construed as illustrative only, and not limiting of the present disclosure in any way whatsoever.
[0107] Material.
[0108] Unless otherwise stated, the following materials were used in the examples: acrylic acid (AA), 99%; acrylamido-2-methylpropanesulfonic acid (AMPS), 99%; 2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (DMAPS), 95%; itaconic acid, 99%; 3-sulfopropyl acrylate potassium salt (SPAK), 96%; 3-sulfopropyl methacrylate potassium salt (SPMK), 98%; potassium persulfate (KPS), ≥99%; N, N-methylene (bis)acrylamide (MBAA), ≥99%; ammonium persulfate (APS), ≥98%; N, N, N', N'-tetramethylethylenediamine (TEMED), ≥99.5%; 3-sulfopropyl methacrylate potassium salt, 98%, 3-sulfopropyl acrylate potassium salt, poly(ethylene glycol) diacrylate (PEGDA), Mw = 250 g / mol; ethylene glycol dimethacrylate (EGDMA), Mw = 198.22 g / mol; and poly(ethylene glycol) dimethacrylate (PEGDMA), Mn = 550 g / mol.
[0109] Comparative Example 1. Preparation of PAA-based SAM particles.
[0110] Add 16 g of milli-Q water to a 200 mL tall reaction flask and dissolve 1.94 g of 97% NaOH pellets for 70% neutralization (or 2.08 g in the case of 75% neutralization) in an ice bath. Add 5 g of AA to the NaOH solution. Dissolve 30 mg of >99% MBAA in 3 mL of water and add to the above solution. Stir the solution with a magnetic stir bar to ensure thorough mixing. Place the reaction flask in a N 2 The gas was purged for 10 min and the temperature was increased to 40 °C. 15 mg of APS (redox initiator) was dissolved in 1 mL of water and added to the reaction mixture along with 10 μL of TEMED. The reaction flask was sealed and kept under low flow of N 2 The reaction mixture was stirred at 40 °C for 1 h. The mixture was stirred at 40 °C for 2 h. The gelation started within 10-20 min. After gelation, the reaction was continued for another 4 hours. The gelled reaction product was cut into small pieces and dried at 85 °C for 48 hours. The dried sample was ground using a coffee grinder. The dried gel particle size fraction between 300-600 microns was separated using a suitable sieve and dried overnight.
[0111] Comparative Example 2. Preparation of AMPS-based SAM particles.
[0112] Add 16 g of milli-Q water to a 200 mL high reaction flask and dissolve 2.08 g of 97% NaOH pellets in water on an ice bath. Add 14.3 g of AMPS and dissolve completely in the reaction mixture. Dissolve 30 mg of >99% MBAA completely in 3 mL of water and add to the above solution. Stir the solution with a magnetic stirrer at about 300 rpm throughout the reaction. Measure the pH of the reaction and adjust to about 4.8-5 by adding 12 M NaOH solution dropwise. Heat the reaction flask with N 2 The gas was purged for 10 min and the temperature was increased to 40 °C. 15 mg of APS (redox initiator) was dissolved in 1 mL of water and added to the reaction mixture along with 10 μL of TEMED. The reaction flask was sealed and kept under low flow of N 2 The reaction mixture was stirred for 4 hours at 40 °C for 1 h. The gelation was continued for 4 hours. The gelled reaction product was cut into small pieces and dried in an oven at 85 °C for 48 hours. The dried sample was ground using a coffee grinder. The dried gel particle size fraction between 300 and 600 microns was separated using a suitable sieve and dried overnight.
[0113] Example 1. Preparation of AA 90%-AMPS 10% based SAM particles.
[0114] 16 g of milli-Q water was added to a 200 mL high reaction flask. 2.08 g of 97% NaOH pellets were dissolved in water on an ice bath. 4.5 g of AA (anhydrous, containing 200 ppm MEHQ as an inhibitor, 99%) was added to the NaOH solution. 1.43 g of AMPS was then added and completely dissolved in the reaction mixture. 30 mg of >99% MBAA was completely dissolved in 3 mL of water and added to the above solution. The solution was stirred with a magnetic stirrer during the entire reaction. The reaction flask was heated with N 2 The gas was purged for 10 min and the temperature was increased to 40 °C. 15 mg of APS (redox initiator) was dissolved in 1 mL of water and added to the reaction mixture along with 10 μL of TEMED. The reaction flask was sealed and kept under low flow of N 2 The reaction mixture was stirred for 4 hours at 40 °C for 1 h. The gelation was continued for 4 hours. The gelled reaction product was cut into small pieces and dried in an oven at 85 °C for 48 hours. The dried sample was ground using a coffee grinder. The dried gel particle size fraction between 300 and 600 microns was separated using a suitable sieve and dried overnight.
[0115] Example 2. Preparation of SAM particles based on AA 90%-SPAK 10%.
[0116] Add 16 g of milli-Q water to a 200 mL high reaction flask. Dissolve 1.87 g of 97% NaOH pellets in water on an ice bath. Add 4.5 g of AA to the NaOH solution. Then add 1.60 g of SPAK and dissolve completely in the reaction mixture. Dissolve 30 mg of >99% MBAA completely in 3 mL of water and add to the above solution. Stir the solution with a magnetic stirrer throughout the reaction. Stir the reaction flask with N 2 The gas was purged for 10 min and the temperature was increased to 40 °C. 15 mg of APS (redox initiator) was dissolved in 1 mL of water and added to the reaction mixture along with 10 μL of TEMED. The reaction flask was sealed and kept under low flow of N 2 The reaction mixture was stirred for 4 hours at 40 °C for 1 h. The gelation was continued for 4 hours. The gelled reaction product was cut into small pieces and dried in an oven at 85 °C for 48 hours. The dried sample was ground using a coffee grinder. The dried gel particle size fraction between 300 and 600 microns was separated using a suitable sieve and dried overnight.
[0117] Example 3. Preparation of SAM particles based on AA 90%-SPMK 10%.
[0118] Add 16 g of milli-Q water to a 200 mL high reaction flask. Dissolve 1.87 g of 97% NaOH pellets in water on an ice bath. Add 4.5 g of AA to the NaOH solution. Then add 1.70 g of SPMK and dissolve completely in the reaction mixture. Dissolve 30 mg of >99% MBAA completely in 3 mL of water and add to the above solution. Stir the solution with a magnetic stirrer throughout the reaction. Stir the reaction flask with N 2 The gas was purged for 10 min and the temperature was increased to 40 °C. 15 mg of APS (redox initiator) was dissolved in 1 mL of water and added to the reaction mixture along with 10 μL of TEMED. The reaction flask was sealed and kept under low flow of N 2 The reaction mixture was stirred for 4 hours at 40 °C for 1 h. The gelation was continued for 4 hours. The gelled reaction product was cut into small pieces and dried in an oven at 85 °C for 48 hours. The dried sample was ground using a coffee grinder. The dried gel particle size fraction between 300 and 600 microns was separated using a suitable sieve and dried overnight.
[0119] Example 4. AUL measurements of SAM particles.
[0120] AUL measures the ability of a polymer to absorb fluid under static load and can be considered a measure of gel swelling combined with gel strength. A typical AUL test format is used, which consists of a simple cylindrical device with a macroporous sintered filter plate at one end of a sintered plastic cylinder. For the sample tested, 160 mg (W 1 ) dried SAP sample and evenly placed on the surface of polyester gauze, which was placed on top of the sintered plastic. The desired load (0.3PSI, 0.6PSI or 0.9PSI) was then placed on top of the dry SAP particles, where the load was designed to allow it to move freely in the plastic cylinder. The device was placed in a petri dish with 0.9% saline solution on top of the screen (to ensure that water could access the bottom of the sintered plastic) for 1 hour. The swollen sample (W 2 ), and use equation (1) to calculate AUL
[0121] (1).
[0122] About 0.160 g of each type of SAM particles prepared according to Comparative Example 1, Comparative Example 2, Example 1, Example 2 and Example 3 were placed in an AUL measuring cup and covered with a lid and a steel cylinder weighing 100 g. The pressure on the SAM particles was 0.3 PSI. The cups were placed in 0.9% saline for 1 hour. The absorbed water was weighed for each cup. The AUL was then calculated by dividing the absorbed water by the weight of the SAM particles. The average 1-hour AUL of the AA-based SAM was 12.4. The average 1-hour AUL of AA / AMPS (87.5% / 12.5%) was 15.4. The average 1-hour AUL of the AMPS-based SAM particles was 11.5.
[0123] These results demonstrate that the AUL of SAM particles based on AA / AMPS copolymers is improved compared to SAM particles based on AA alone and SAM particles based on AMPS alone.
[0124] Example 5. Synthesis of copolymer compositions.
[0125] A variety of novel copolymer compositions were synthesized by replacing a portion of AA (5, 10, 15, 20, 25, or 30 mol % of the total monomers present in the backbone) with different monomers using free radical copolymerization in water to prepare copolymer hydrogels. Unless otherwise stated, acrylic acid was partially neutralized (70%), N, N′-methylene (bis) acrylamide (99% purity) was used as a crosslinker (0.21 - 0.23 mol % relative to total monomers), and potassium persulfate (≥99.0% purity) was used as a thermal initiator (0.08 - 0.1 mol % relative to total monomers).
[0126] Each polymerization reaction was performed according to the following procedure. A 200 mL glass beaker was immersed in an ice bath. NaOH pellets were dissolved in milli-Q water and acrylic acid was added. For each series of reactions, stock solutions of crosslinker (10 mg / mL) and initiator (20 mg / mL) of defined concentrations were freshly prepared before each synthesis. The required amount of crosslinker was added to each reaction mixture, after which the mixture was purged with nitrogen for 5-10 minutes and the temperature was increased. The beaker was sealed and kept under a low nitrogen flow to ensure inert conditions throughout the polymerization process. The reaction was allowed to proceed for about 4 hours, although macroscopic gelation of most samples was observed within 10-15 minutes. The prepared gel was cut into smaller pieces and dried in an oven at 85°C for 48 hours. The dried gel was ground and sieved, and all particles for subsequent testing were collected between 600 µm and 300 µm standard sieves.
[0127] The specific motivations for the selected comonomers and details of their respective syntheses are as follows.
[0128] AMPS
[0129] Although AMPS has an acrylamide-based backbone structure and therefore does not completely copolymerize with AA randomly, the monomer is an inexpensive and commercially available hydrophilic sulfonic acid-based monomer that has a permanent charge at pH values far below physiological pH, thereby providing high hydrophilicity and anionic properties over a wide pH range. The side chains also contain anionic charges that are spaced farther from the backbone under aqueous conditions and are therefore less likely to significantly affect the degree of ionization of adjacent acrylic acid residues, where the charged residues are closer to the polymer backbone.
[0130] The hydrogels were prepared using the general conditions described above. Since AMPS is a strong acid, it was calculated to achieve 70% or 75% total ionization (AMPS + AA, corresponding to all AMPS and based on the pK values of the two monomers). a AMPS was added to the neutralized mixture after the NaOH pellets and acrylic acid were completely dissolved in water. Gelation occurred in less than 10 minutes, although the reaction was continued for another 4 hours. All prepared gels appeared transparent and were neither sticky nor too brittle. The gels remained transparent when dry, although a slight yellow tint was observed, which disappeared when the gel was rehydrated.
[0131] SPAK
[0132] 3-Sulfopropyl acrylate potassium salt (SPAK) is an acrylate monomer with a sulfate group tethered away from the polymer backbone that readily copolymerizes with acrylic acid and, given their similar polymerizable groups, can potentially produce copolymers with AA with a high degree of randomness.
[0133] Hydrogels were prepared using the general conditions described above and the degree of neutralization was calculated as described for AMPS. Gelation occurred within 10-15 minutes, although the reaction was continued for more than 4 hours. All gels prepared appeared transparent and were neither sticky nor too brittle. The gels remained transparent when dried, although a slight yellow tint was observed, which disappeared when the gel was rehydrated.
[0134] SPMK
[0135] 3-Sulfopropyl methacrylate potassium salt (SPMK) has the same spacer and tethered sulfate groups as SPAK, but has polymerizable methacrylate groups instead of acrylate groups. Likewise, while SPMK can readily copolymerize with acrylic acid, the backbone will be somewhat sterically hindered, and the polymerizable groups of the monomer may react at a different rate than AA. This difference may result in fewer random copolymers with AA compared to SPAK, but with the sulfate groups tethered at the same distance from the polymer backbone.
[0136] Hydrogels were prepared using the general conditions described above and the degree of neutralization was calculated as described for AMPS. Gelation occurred within 10-15 minutes, although the reaction was continued for more than 4 hours. All gels prepared appeared transparent and were neither sticky nor too brittle. The gels remained transparent when dried, although a slight yellow tint was observed, which disappeared when the gel was rehydrated.
[0137] DMAPS
[0138] Sulfobetaine is an important class of zwitterionic structures containing quaternary ammonium and sulfonate groups. Due to the presence of these positively and negatively charged groups within the same repeating unit, sulfobetaine hydrogels can maintain a constant near-zero net charge, regardless of the pH of the medium. Sulfobetaine monomers also bind extremely large amounts of water (up to 14 water molecules per repeating residue), a highly hydrated state that persists even in high ionic strength media such as urine or blood.
[0139] The hydrogels were prepared using the general conditions described above. Gelation was observed in all samples in less than 15 minutes. The appearance of the prepared gels was transparent. During the drying process, the gels shrank and became slightly yellow in appearance, but remained transparent. The dried gels were very easy to grind, and a high percentage of fine particles was observed.
[0140] VSA
[0141] Vinyl sulfonic acid is a highly reactive unsaturated sulfonic acid. It is a colorless, water-soluble liquid, although commercial samples may appear yellow or even red. Polyvinyl sulfonic acid (PVSA; as the sodium salt) is a blood-compatible polyelectrolyte with negatively charged sulfonate groups. Relative to AMPS, the anionic functional groups (also fully charged at physiological pH) are significantly closer to the polymer backbone, similar in distance to the -COOH groups in AA residues. Therefore, this monomer was chosen to evaluate any differences in swelling observed depending on how far away from the backbone the charged groups are tethered.
[0142] The hydrogel was prepared using the general conditions described above. Gelation occurred quickly (in about 15 minutes) to produce a clear but extremely viscous gel that was difficult to remove from the beaker. During the drying process, the gel remained viscous and turned pale yellow while remaining transparent. Due to its viscous nature, the gel was also difficult to grind.
[0143] Example 6. AUL and CRC results for copolymer compositions.
[0144] The swelling results, i.e., absorption under load (AUL) and centrifuge retention capacity (CRC), of the copolymer compositions prepared according to Example 3 are presented in Table 1. These copolymer compositions were prepared with different functional comonomers (initiator: KPS, temperature: 70°C). The incorporated monomers included acrylic acid (AA), 2-acrylamido-2-methylpropane sulfonic acid (AMPS), 3-sulfopropyl acrylate potassium salt (SPAK), 3-sulfopropyl methacrylate potassium salt (SPMK), [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (DMAPS) and vinyl sulfonic acid (VSA).
[0145] AUL was measured according to the procedure of Example 4.
[0146] In contrast to the AUL test, in which a dry powder of SAP is hydrated under load, the CRC test measures the ability of a pre-swollen SAP to retain water under force. 1 ) Dry SAP samples were weighed into pre-weighed tea bags. The tea bags were immersed in 0.9 saline solution for 1 hour to swell the SAP. Subsequently, the tea bags were placed in cylindrical centrifuge tubes with porous interiors to allow drainage and centrifuged at 1600 rpm for 3 minutes. As a control, empty tea bags were also placed in saline and centrifuged at the same speed. After centrifugation, the tea bags were weighed again (W 2 ), and calculate the difference between the dry sample and the swollen sample. The CRC amount is calculated by equation (2):
[0147] (2).
[0148] All AUL measurements reported represent the average of 2-3 replicates per batch. Where more than one AUL number is reported, the second number represents an independent replicate batch. CRC was measured using a 100 g weight.
[0149] Table 1. AUL and CRC results of copolymer superabsorbent hydrogels prepared with different functional comonomers.
[0150]
[0151] The swelling results showed that the AUL increased with most of the synthesized copolymers compared to the control hydrogels. This result clearly demonstrates the benefit of copolymerizing monomers with different types of charges (particularly AMPS, SPAK, and SPMK) into AA-based SAPs. SPAK and SPMK can produce hydrogels with particularly high AUL values, which are up to 38% higher than the AUL values obtained with the AA-only control.
[0152] Copolymerization appears to reduce the CRC of most hydrogels, with most copolymers resulting in a reduction in CRC of approximately 10%-25%. This opposing trend in CRC and AUL is consistent with conventional observations, although minimizing this CRC reduction is desirable. However, certain compositions (e.g., AA 87.5% / AMPS 12.5% with a crosslinker content of 0.31 mol% and AA 82.5% / AMPS 17.5% with a crosslinker content of 0.31 mol%) showed relatively minimal CRC reductions (approximately 10%-15%) while still showing an increase in AUL of more than 20%.
[0153] Mixing methacrylate monomers with tethered sulfate groups (AMPS, SPAK, SPMK) with AA is a promising strategy to increase AUL, while the introduction of vinyl sulfate monomers (VSA) in which the charge is close to the backbone leads to similar or slightly reduced AUL, accompanied by a significant reduction in CRC. Therefore, the backbone structure of the monomer or the distance between the backbone and the charged sulfate groups substantially changes the properties of the SAP.
[0154] Copolymerization of the zwitterionic monomer DMAPS did not appear to give a significant benefit over the AA control.
[0155] Incorporation of AMPS into the hydrogels consistently increased the measured AUL compared to any relevant AA control.
[0156] Example 7. Effect of cross-linker length.
[0157] To evaluate the effect of cross-linker length on SAP performance, the performance of hydrogels prepared with PEG diacrylate-based cross-linkers with various PEG chain lengths was analyzed for AA-co-AMPS copolymers. An AA-only control was also prepared using the same cross-linker type / amount to enable direct comparison of the observed swelling responses.
[0158] Hydrogels were prepared using the same protocol generally used for each comonomer mixture, but replacing the MBAA content with PEGDA, EGDMA, or PEGDMA at the same molar ratio. Gelation occurred within a few minutes to produce clear gels, although the hydrogels crosslinked by EGDMA and PEGDMA were slightly more viscous than the control.
[0159] It was determined that higher AUL values can be achieved by using higher crosslink density. However, consistently significant AULs were observed at 70%, 75%, or 80% neutralization. This relative independence of the degree of neutralization is a process-related benefit of formulating SAPs using the AMPS copolymerization process, as hydrogels containing only AA are more sensitive to the degree of neutralization of the reaction mixture.
[0160] Example 8. Incorporation of multiple charges on the same monomer.
[0161] To evaluate the possibility of incorporating two anionic charges on the same monomer unit, itaconic acid (IA) copolymers of AA and AA-co-AMPS were evaluated. The AUL and CRC properties of the hydrogels incorporating IA are shown in Table 2.
[0162] Table 2. Properties of copolymers incorporating two anionic charges.
[0163]
[0164] IA cannot crosslink with MBAA under the same conditions as AA. Homopolymerization of IA is hindered by the allylic hydrogen atoms within IA that can act as chain transfer agents, with the copolymerization rate of IA strongly dependent on both pH and the degree of ionization of IA. However, by switching the crosslinker to PEGDA, gelation can be achieved. The resulting gels are significantly more viscous than control gels of either AA or AA-co-AMPS alone, and show significantly reduced AUL values compared to either gel, although significantly higher CRCs are obtained.
[0165] The results presented here demonstrate that copolymerization of monomers with different types of charge significantly alters the absorbency of AA-based hydrogels. Copolymer hydrogels of AA and AMPS show an optimal combination of good performance (significantly higher AUL and matching CRC compared to relevant controls) and ease of synthesis.
[0166] This written description uses examples to illustrate the disclosure, including the best mode, and also to enable any person skilled in the art to practice the disclosure, including making and using any compositions or systems and performing any included methods. The patentable scope of the disclosure is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have elements that do not differ from the literal language of the claims, or if they have equivalent elements with insubstantial differences from the literal language of the claims.
[0167] As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," "contains," "containing," "characterized by," or any other variation thereof, are intended to cover a non-exclusive inclusion, subject to any expressly indicated limitation. For example, a composition, mixture, process, or method that comprises a list of elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, mixture, process, or method.
[0168] The transitional phrase "consisting of" excludes any elements, steps, or ingredients not specified. If in a claim, this would make the claim close to including materials other than those recited in addition to the impurities normally associated therewith. When the phrase "consisting of" appears in a clause in the body of a claim, rather than immediately following a preamble, it is limited only to the elements set forth in that clause; other elements are not excluded from the claim as a whole.
[0169] The transitional phrase "consisting essentially of is used to define a composition or method that includes materials, steps, features, components, or elements in addition to those literally disclosed, provided that such additional materials, steps, features, components, or elements do not materially affect the basic and novel characteristics of the claimed invention. The term "consisting essentially of occupies an intermediate position between "comprising" and "consisting of."
[0170] When an invention or a portion thereof is defined using an open-ended term such as "comprising," it should be readily understood that (unless otherwise indicated) the specification should be interpreted as also describing the invention using the term "consisting essentially of" or "consisting of."
[0171] In addition, unless expressly stated to the contrary, "or" refers to an inclusive or rather than an exclusive or. For example, the condition A or B satisfies any of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).
[0172] In addition, the indefinite articles "a" and "an" before the elements or components of the present invention are intended to be non-restrictive with respect to the number of instances (i.e., occurrences) of the elements or components. Therefore, "a" or "an" should be understood to include one or at least one, and the singular word form of an element or component also includes the plural, unless the number obviously means the singular.
[0173] As used herein, the term "about" means plus or minus 10% of a value.
Claims
1. A superabsorbent polymer, comprising A copolymer comprising a major portion of low molecular weight monomers, each of which individually comprises a backbone and a charged moiety, wherein the major portion is present in an amount greater than 60 mole percent of the copolymer, and wherein each individual low molecular weight monomer has a molecular weight of less than 150 g / mol; a minor portion of high molecular weight monomers, each of which individually comprises a backbone and a charged moiety, wherein the minor portion is present in an amount less than 40 mole percent of the copolymer, and wherein each individual high molecular weight monomer has a molecular weight greater than 150 g / mol; and a crosslinking agent, wherein the crosslinking agent density is in the range of 0.05 mol % to 1 mol %; wherein the average distance between the main chain and the charged moiety of each individual low molecular weight monomer is smaller than the average distance between the main chain and the charged moiety of each individual high molecular weight monomer, wherein the copolymer lacks a structured ordered arrangement of the low molecular weight monomer and the high molecular weight monomer, wherein the superabsorbent polymer is prepared by free radical polymerization, wherein free radicals are provided by thermal decomposition in the free radical polymerization, and wherein the free radical polymerization is carried out in an inert atmosphere.
2. The superabsorbent polymer of claim 1, wherein the superabsorbent polymer is in the form of a gel, a liquid, a solid, a paste or a combination thereof.
3. The superabsorbent polymer of claim 1, wherein the superabsorbent polymer is in the form of particles, fibers, beads or a combination thereof.
4. The superabsorbent polymer of claim 1, wherein the superabsorbent polymer is in the form of particles having a diameter ranging from 100 μm to 1000 μm.
5. The superabsorbent polymer of claim 1, wherein the superabsorbent polymer is surface cross-linked.
6. The superabsorbent polymer of any one of claims 1 to 5, wherein the average distance between the main chain and the charged portion of each individual low molecular weight monomer is less than 5 angstroms, and the average distance between the main chain and the charged portion of each individual high molecular weight monomer is greater than 5 angstroms.
7. A superabsorbent polymer as claimed in any one of claims 1 to 5, wherein each individual high molecular weight monomer is selected from the group consisting of 2-acrylamido-2-methylpropane sulfonic acid, 3-sulfopropyl methacrylate, 3-sulfopropyl acrylate, acrylate or methacrylate monomers with tethered sulfate groups and their salts, salts of vinyl-linker-acid units and vinyl sulfate monomers.
8. The superabsorbent polymer of any one of claims 1 to 5, wherein each individual low molecular weight monomer is selected from the group consisting of acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl phosphoric acid, partially hydrolyzed maleic anhydride, and combinations thereof.
9. A method for preparing a superabsorbent polymer, the superabsorbent polymer comprising A copolymer comprising a major portion of low molecular weight monomers, each of which individually comprises a backbone and a charged moiety, wherein the major portion is present in an amount greater than 60 mole percent of the copolymer, and wherein each individual low molecular weight monomer has a molecular weight of less than 150 g / mol; a minor portion of high molecular weight monomers, each of which individually comprises a backbone and a charged moiety, wherein the minor portion is present in an amount less than 40 mole percent of the copolymer, and wherein each individual high molecular weight monomer has a molecular weight greater than 150 g / mol; and a crosslinking agent, wherein the crosslinking agent density is in the range of 0.05 mol % to 1 mol %; wherein the average distance between the backbone and the charged moiety of each individual low molecular weight monomer is less than the average distance between the backbone and the charged moiety of each individual high molecular weight monomer, wherein the copolymer lacks a structured ordered arrangement of the low molecular weight monomers and the high molecular weight monomers, wherein the method is a free radical polymerization method, the method comprising: forming a mixture comprising Solvents; A low molecular weight monomer comprising a backbone and a charged moiety; a high molecular weight monomer comprising a backbone and a charged moiety; and Cross-linking agent; Initiating the reaction by adding a thermal initiator and optionally a accelerator, wherein the thermal initiator provides free radicals by thermal decomposition; and The mixture was allowed to react in an inert atmosphere.
10. The method of claim 9, wherein the method step of reacting the mixture comprises heating the mixture.
11. The method of claim 9, further comprising drying the reaction product.
12. The method of claim 9, further comprising grinding the reaction product.
13. A method of using a superabsorbent polymer, the superabsorbent polymer comprising A copolymer comprising a major portion of low molecular weight monomers, each of which individually comprises a backbone and a charged moiety, wherein the major portion is present in an amount greater than 60 mole percent of the copolymer, and wherein each individual low molecular weight monomer has a molecular weight of less than 150 g / mol; a minor portion of high molecular weight monomers, each of which individually comprises a backbone and a charged moiety, wherein the minor portion is present in an amount less than 40 mole percent of the copolymer, and wherein each individual high molecular weight monomer has a molecular weight greater than 150 g / mol; and a crosslinking agent, wherein the crosslinking agent density is in the range of 0.05 mol % to 1 mol %; wherein the average distance between the backbone and the charged moiety of each individual low molecular weight monomer is less than the average distance between the backbone and the charged moiety of each individual high molecular weight monomer, wherein the copolymer lacks a structured ordered arrangement of the low molecular weight monomers and the high molecular weight monomers, wherein the superabsorbent polymer is prepared by free radical polymerization, wherein free radicals are provided by thermal decomposition in the free radical polymerization, and wherein the free radical polymerization is carried out in an inert atmosphere, and the method comprises using the superabsorbent polymer in a consumer product.
14. The method of claim 13, wherein the superabsorbent polymer is in the form of particles having a diameter in the range of 100 μm to 1000 μm.
15. The method of claim 13, wherein the consumer product is selected from the group consisting of cloth products, feminine hygiene napkins, and disposable mattress pads.
16. The method of claim 13, wherein the consumer product is a diaper.